Effect of tool rotational speed on the friction stir welded aluminum alloys: A review. (2022) - Amatullah, Mouminah; Jan, Mehwish; Farooq, Munazah; Zargar, Afra Saeed; Maqbool, Annayath; Khan, Noor Zaman
Abstract: In contemporary world, leading industries such as automotive and aviation are using aluminium alloys due to its high strength to weight ratio. Conventional welding methods such as fusion arc welding causes solidification and liquid cracking in aluminium alloys. Friction Stir Welding (FSW), a solid state process has gained stupendous reputation in welding industry by successfully joining aluminium alloys with no obvious defects. The process parameters such as tool rotational speed, tool traverse speed and tool geometry plays a significant role in obtaining defect free welds and in increasing the joint efficiency. Tool rotational speed greatly influences the material movement and heat generation in FSW. This paper highlights the effect of rotational speed on mechanical and microstructural properties of the various aluminium alloys. The role of tool rotational speed in elimination of defects such as tunnel and kissing bond has also been discussed.